1989
DOI: 10.1002/j.1460-2075.1989.tb03358.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of an N-terminal regulatory domain of the c-abl tyrosine kinase activates its oncogenic potential.

Abstract: The requirements for the oncogenic conversion of the c‐abl proto‐oncogene have been determined by the expression of N‐terminal deleted forms and viral gag‐fused forms of the c‐abl proteins from a selectable retroviral vector. To activate the transforming potential of c‐abl, it is necessary that (i) specific N‐terminal amino acids are deleted to release the kinase from negative regulation in vivo; (ii) an N‐terminal myristylation site is part of the activated kinase; (iii) the fatty‐acylated, activated kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(176 citation statements)
references
References 48 publications
6
168
0
2
Order By: Relevance
“…Because the Abl SH3 domain has been implicated in the repression of c-Abl activity (Barila and SupertiFurga, 1998;Franz et al, 1989;Jackson and Baltimore, 1989;Van Etten et al, 1995), and has been shown to bind to Cbl (Shishido et al, 2000), we examined whether the PRD1 region of Cbl speci®cally interacts with the Abl SH3. As shown in Figure 3a, the SH3 domain of Abl bound directly to full-length Cbl, but not to deletion mutants lacking PRD-1, when assayed in`far-Western' ®lter-binding experiments.…”
Section: Cbl Engages C-abl and Is Phosphorylated By Itmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the Abl SH3 domain has been implicated in the repression of c-Abl activity (Barila and SupertiFurga, 1998;Franz et al, 1989;Jackson and Baltimore, 1989;Van Etten et al, 1995), and has been shown to bind to Cbl (Shishido et al, 2000), we examined whether the PRD1 region of Cbl speci®cally interacts with the Abl SH3. As shown in Figure 3a, the SH3 domain of Abl bound directly to full-length Cbl, but not to deletion mutants lacking PRD-1, when assayed in`far-Western' ®lter-binding experiments.…”
Section: Cbl Engages C-abl and Is Phosphorylated By Itmentioning
confidence: 99%
“…Normally c-Abl activity is tightly repressed, as overexpression does not lead to e cient transformation or increased tyrosine phosphorylation of cell proteins (Franz et al, 1989;Jackson and Baltimore, 1989). This negative regulation is mediated at least in part by the SH3 domain, as deleting, mutating, or altering the position of the SH3 is su cient to activate the kinase and transforming activities of Abl (Franz et al, 1989; Jackson and Baltimore, 1989;Mayer and Baltimore, 1994;Van Etten et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The SH3 domain seems to be responsible for the functional inactivity of the ABL-portion of BCR/ABL. Hence, we created a mutant that lacks a functional SH3 domain (DSH3-ABL) alone and in combination with the T315I.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that N-terminal mutations, especially within the SH3 domain, can activate the transforming activity of the normally nontransforming c-src and c-abl gene products (25)(26)(27)(28)(29) raised the possibility that SH3 might bind a kinase inhibitor. Ifthis were the case, the overexpressed SH3 domain of p47gam-crk might be expected to compete away such an inhibitor, leading to kinase activation in vivo.…”
mentioning
confidence: 99%